NILAI TUKAR RUPIAH DAN KINERJA PASAR SAHAM: STUDI EMPIRIK PADA BURSA SAHAM INDONESIA - Siti Saadah (University of Merdeka Malang, 2016)
This study examines the impact of rupiah exchange rate movement to the stock market performance in Indone-sia, using a dailytime series data from January 2013-December, 15, 2015. Data shows that the characteristic of volatility clustering (heteroskedastic) is the reason for applicating TGARCH estimation method in this study. By applicating this method, it shows that the fluctuation of rupiah is in a quite deep depreciation during the period of this analysis, although the cause of stocks return declined but did not lead to investment in Indonesia capital market becomes more risky. This is reflected in the empirical findings of this study, that the volatility of stock returns in the Indonesia Stock Exchange does not increase significantly due to the deprecia-tion trend experienced during the analysis period.